LESSON STUDY DALAM MEMBANGUN LEARNING ORGANISATION MADRASAH - ., Sholikin (Inovasi: Jurnal Diklat Keagamaan, 2017)
Being the centre of excellent, madrasahs have to develop theirHuman Resources, due to the increasing of society demands.They have to improve not only cognitive and skill competence butalso their attitude. This article offers madrasah to be a LearningOrganization, in which madrasah always promotes ContinuouseProfessional Development (CPD) for their Human Resource (teachers)by faciliting their teachers several activities. Lesson Study offersa lot of activities which enables teachers share their knowledgeand skill through ”Plan, Do and See”. By implementing LS madrasahthe teacher will get a lot of beneficial, such as defining learning goal,implementing a certain teaching model and how to evaluate theteaching and learning process. All of those will lead us to what wecalled as a Learning Organisation.